A compressor based 16-bit binary-to-residue converter for low power applications - Vasuma, Narayana (2014)
With the growing demand for low-power, high-speed electronic devices it has become vital to ensure that all arithmetic modules used in the digital system are power, speed and area-efficient. Arithmetic operations such as addition, multiplication etc. are increasingly using the residue number system representation to increase the speed of computing. This neccessitates the need for binary-to-residue and residue-to-binary converter systems. This project mainly deals with the design of a low-power, high-speed binary-to-residue converter architecture based on compressor blocks.